Introducing the American Society for Bone and Mineral Research multistakeholder group secondary fracture prevention recommendations: Nurse practitioners play an important role. Issue 2 (3rd February 2022) - Alexander, Ivy M.; Bowka, Linda; Hannafon, Freda; Lake, Anne; Williams, Kathy; Woodburn, Marcia
ABSTRACT: Sequelae after an osteoporosis-related fracture include significant morbidity and mortality. Preventing repeat fractures is an important aspect of mitigating these sequelae. As highlighted in the American Society for Bone and Mineral Research multistakeholder coalition's Secondary Fracture Prevention: Consensus Clinical Recommendations, nurse practitioners play an important role in secondary fracture prevention. With a focus on education, longitudinal relationships with patients, and expertise in coordinating and managing care, nurse practitioners are uniquely qualified to run Fracture Liaison Services and help close the gap to care in secondary fracture prevention.